Kinerja Pertumbuhan Benih Ikan Lele (Clarian gariepinus) Yang Diberi Prebiotik Ekstrak Umbi Sarang Semut (Myrmecodia pendans) dan Probiotik Lacticaseibacillus paracasei - Meiana Olivia Sinaga; Irawadi Gunawan; Ricky Djauhari; Maryani Maryani; Murrod C Wirabakti (Jurnal Akuakultur Sungai dan Danau, 2022)
This study aimed to evaluated the growth performance of dumbo catfish (Clarias gariepinus). In this study, ant nest tuber extract and probiotic Lacticaseibacillus paracasei were mixed into feed with the coated method without the addition of ant nest tuber extract and probiotic Lacticaseibacillus paracasei (A), 1% ant nest tuber extract (B), probiotic Lacticaseibacillus paracasei 1% (C). and a combination of ant nest tuber extract and probiotic Lacticaseibacillus paracasei each 1% (D). Fish with an initial body weight of 1.5 - 2 g were kept in 3 ponds (15x10x1.5) m3 with a total of 12 hapa nets measuring 1x1x1 (m3) (45 fish / hapa nets). Fish were fed treatment with three replications for 35 days. The best feed efficiency, feed conversion ratio, daily growth rate and absolute weight growth were found in the African catfish fry group that consumed a combination of feed supplementation with 1% dose of ant nest tuber extract and 1% dose of probiotic Lacticaseibacillus paracasei, each of 185.47%. , 0,55,7,79%, and 20,80 gr